Activated porous carbon supported Pd and ZnO nanocatalysts for trace sensing of carbaryl pesticide in water and food products. (4th July 2022) - Jemai, Rihem; Djebbi, Mohamed Amine; Hussain, Navid; Yang, Bingquan; Hirtz, Michael; Trouillet, Vanessa; Ben Rhaiem, Hafsia; Ben Haj Amara, Abdesslem
Abstract : Pd/ZnO/APC nanocomposite-modified glassy carbon electrode (GCE) for voltammetric detection of carbaryl pesticides. Abstract : Nanomaterials-based sensors are direly needed as a monitoring tool for the credible and accurate determination of pesticides in water and food samples. Herein, electrocatalysts of Pd and ZnO nanoparticles (NPs) supported on a highly porous framework of activated carbons (APC) were prepared for efficient electrochemical detection of carbaryl trace. First, activated potato starch was used as a pyrolysis precursor to obtain APC. The ZnO NPs were then grown on the APC substrate by sol–gel/impregnation methods, followed by in situ reduction of Pd NPs. The as-prepared nanocomposite of Pd/ZnO/APC was morphologically and structurally confirmed by systematic physicochemical analysis. As-fabricated Pd/ZnO/APC nanocomposites were later evaluated for the efficient sensing of carbaryl by modifying a glassy carbon electrode (GCE). Cyclic voltammetry analysis revealed the unique oxidative sensing ability of Pd/ZnO/APC for carbaryl at 0.62 V with a low Δ E (80 mV) as compared to that of bare GCE. Based on the notable sensing ability of Pd/ZnO/APC, a reliable and sensitive electrochemical method was anticipated for the quantitative and qualitative determination of carbaryl. Meanwhile, experimental parameters, including electrolyte environment and electrodeposition conditions, were carefully refined to achieve maximum sensitivity and low detection limits. Under optimized conditions, the electrochemical sensing of carbaryl was realized with an LOD of 0.01 μM and a detection range of 0.01–5.0 μM. Moreover, the sensing electrode exhibited excellent selectivity, good reproducibility, and long-term stability, which qualified the sensor to analyze real samples, where it also showed satisfactory performance.